Implementation Of Game Based Learning Strategies To Improve Student Understanding In PAI Learning At Cowek II Elementary School - Hidayah, Nadia Nurul; Sholikhudin, M. Anang (Yayasan Rahmat Islamiyah, 2025)
This study aims to evaluate the effectiveness of the implementation of Game Based Learning (GBL) in improving students' understanding of Islamic Religious Education (PAI) subjects at SDN Cowek II. The research method used is qualitative with data collection techniques through observation and in-depth interviews. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and verification. The results of the study indicate that the implementation of the GBL strategy is able to create an interactive and enjoyable learning atmosphere, and encourage students to be more active and confident in understanding religious material. This strategy not only improves the cognitive aspect, but also has a positive impact on the affective and social aspects of students.